2018
DOI: 10.1055/s-0038-1666870
|View full text |Cite
|
Sign up to set email alerts
|

Elevating Endogenous Sphingosine-1-Phosphate (S1P) Levels Improves Endothelial Function and Ameliorates Atherosclerosis in Low Density Lipoprotein Receptor-Deficient (LDL-R−/−) Mice

Abstract: We conclude that raising endogenous S1P levels exerts anti-atherogenic effects in LDL-R mice that are mediated by favourable modulation of endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…Obviously, there is an inconsistency whether iS1P acts dependent on S1P receptors or not. Moreover, a study using intravital microscopy in a murine atherosclerosis model revealed that iS1P reduced leukocyte adhesion to capillary wall and decreased LPS-induced endothelial permeability [61], thus corroborating our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Obviously, there is an inconsistency whether iS1P acts dependent on S1P receptors or not. Moreover, a study using intravital microscopy in a murine atherosclerosis model revealed that iS1P reduced leukocyte adhesion to capillary wall and decreased LPS-induced endothelial permeability [61], thus corroborating our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Its circulating levels increase with obesity as well as upon fasting and correlate positively with markers of insulin resistance and inflammation (276,283,(346)(347)(348)(349)(350)(351). S1P directly acts on adipose tissue stromal cells to increase proliferation and decrease adipogenic differentiation, prompts adipocytes to increase inflammatory marker expression, triggers hepatocytes to increase inflammatory marker expression, survival, glucose uptake, and lipid accumulation, and leads to an overall decrease in insulin sensitivity (276,348,350,(352)(353)(354)(355)(356)(357)(358)(359)(360)(361). It also triggers skeletal muscle cells to increase glucose uptake, -cells to increase survival and glucosestimulated insulin secretion, vascular smooth muscle cells to increase tone, and endothelial cells to increase immune cell adhesion and permeability (276,348,350,(352)(353)(354)(355)(356)(357)(358)(359)(360)(361).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…S1P directly acts on adipose tissue stromal cells to increase proliferation and decrease adipogenic differentiation, prompts adipocytes to increase inflammatory marker expression, triggers hepatocytes to increase inflammatory marker expression, survival, glucose uptake, and lipid accumulation, and leads to an overall decrease in insulin sensitivity (276,348,350,(352)(353)(354)(355)(356)(357)(358)(359)(360)(361). It also triggers skeletal muscle cells to increase glucose uptake, -cells to increase survival and glucosestimulated insulin secretion, vascular smooth muscle cells to increase tone, and endothelial cells to increase immune cell adhesion and permeability (276,348,350,(352)(353)(354)(355)(356)(357)(358)(359)(360)(361). SPHK1-deficient mice display decreased circulating S1P levels and are variably reported to exhibit either decreased WAT inflammation, liver inflammation and steatosis, and improved glucose tolerance and insulin resistance or increased -cell death and worsened glucose tolerance and insulin sensitivity (349,356,357,359).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…S1P signaling has emerged as an important regulator of cardiac and vascular homeostasis [10] and has reportedly been related to the pathogenesis of multiple cardiovascular outcomes, including coronary artery disease, atherosclerosis, myocardial infarction, and/or HF [11,[52][53][54][55][56][57][58][59][60][61][62][63]. In addition to the effects of S1P on atherosclerosis, which is regarded as a major mechanism involved in ischemic cardiovascular burden, a protective role of S1P on injured myocardium elicited by nonischemic causes has also been suggested [64][65][66].…”
Section: The Effect Of S1p On the Cellular Mechanisms Involved In Carmentioning
confidence: 99%